Synthesis and Antimicrobial Studies of New Spiropyran Quinazolinone Derivatives with Amide, Urea, and Sulfonamide Moieties. (14th September 2017) - Poojari, Subba; G, Krishnamurthy; P, Parameswar Naik; K.S, Jithendra Kumara; N, Sunil Kumar; Naik, Satish
Abstract : Three new series of quinazolinone derivatives containing amide, urea, and sulfonamide were synthesized through multistep synthesis. The required intermediates 4‐[(4′‐oxo‐2, 3, 3′, 4′, 5, 6‐hexahydro‐1′ H ‐spiro[pyran‐4, 2′‐quinazolin]‐1′‐yl)methyl]benzoic acid4 and 1′‐(3‐aminobenzyl)‐2, 3, 5, 6‐tetrahydro‐1′ H ‐spiro[pyran‐4, 2′‐quinazolin]‐4′(3′ H )‐one8 were prepared by hydrolysis of ester and reduction of nitro intermediates. Three different series of compounds were synthesized from these two scaffolds. The key scaffolds4 and8 were successfully converted to target molecules via amides5a –k, urea9a –f, and substituted sulfonamides10a –e . The chemical structures of newly synthesized compounds were characterized by spectral analysis. The structure of5d was confirmed by X‐ray crystallography study. These newly synthesized compounds were screened for antibacterial studies against Staphylococcus epidermidis, Salmonella typhi, Proteus mirabilis, and Shigella sonnei and for the antifungal activity against Aspergillus niger and Candida albicans . Among all the compounds, 9b –d showed excellent activities against S. typhi . Compound9a showed moderate activity against all fungi stains, and5I showed moderate activity against P. mirabilis, while the other derivatives showed fairly good activities. Abstract :